Ancient Sailing Scripture of Sampang Bulan - Ali, Ismail (ASPENSI in Bandung, Indonesia, 2011)
ABSTRACT: A Bajau ancient sailing scripture owned by a famous Bajau sailor of Sabah called âKitab Pelayaran Sampang Bulan (Sappit)â was discovered in Bum-Bum Island, Semporna, Sabah, Malaysia in 2009. The scripture is now kept by his great grandchild, Tuan Hj. Bakara Maharaja Onnong, who is living in Bum-Bum Island. The scripture shows that the Bajau community was definitely the famous sailor of its time in Sabah as well as in the âDunia Melayuâ (Malay World). They had knowledge, understanding and practising tradisional science, and Islamic Mathematics in their daily life. Based on previous studies, the content and the physical form of this scripture show that it is the only ancient sailing guide and also the oldest scripture ever found in the traditional maritime history of Sabah. The scripture and calendar show that Bajau sailors living in islands and coasts of Sabah, before and during the Sulu Sultanateâs era, have already possessed the significant knowledge and understanding on falaq that is outdated according to the Westerners.KEY WORDS: Ancient sailing scripture, Sampang Bulan, Bajau sailors, people science, Ismalic Mathematics, and traditional maritime history.About the Author: Assoc. Prof. Dr. Ismail Ali is a Senior Lecturer at the History Program, School of Social Sciences UMS (Malaysia University of Sabah), Beg Berkunci, Kota Kinabalu, Sabah, Malaysia. He can be reached at: ismailrc@ums.edu.myHow to cite this article? Ali, Ismail. (2011). âAncient Sailing Scripture of Sampang Bulanâ in TAWARIKH: International Journal for Historical Studies, Vol.2(2) April, pp.147-160. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 5, 2011); Revised (March 9, 2011); and Published (April 28, 2011).